The use of films in improving students' vocabulary is effective for enhancing students' vocabulary at SMP NEGERI 4 Motoling : Penggunaan film dalam meningkatkan kosakata siswa terbukti efektif untuk memperbaiki kosakata siswa di SMP Negeri 4 Motoling - Barrylyn S.H. Kussoy; James Ed. Lalira (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to enhance the vocabulary skills of seventh-grade students at SMP Negeri 4 Motoling through the storytelling method. The research employs Classroom Action Research (CAR) with a cycle approach, involving two cycles. Each cycle consists of planning, implementing, observing, and reflecting phases. The storytelling method was integrated into English lessons, with simplified stories and vocabulary-focused activities. Pre-tests and post-tests, along with observation checklists and student interviews, were used for data collection. In Cycle 1, students' mean vocabulary scores improved from 63.6 in the pre-test to 74.8 by the end of the cycle, but the success criteria of 75 were not met. Following reflections and adjustments, Cycle 2 showed significant progress, with mean scores rising to 77 in Meeting 1 and 81.2 in Meeting 2. The percentage of students achieving 'good' and 'very good' ratings increased markedly.The storytelling method effectively improved vocabulary acquisition. Adjustments based on Cycle 1’s feedback, such as simplifying stories and allowing more time for vocabulary practice, contributed to the success in Cycle 2. Students engaged more actively with the content, leading to better understanding and retention of vocabulary. The findings suggest that incorporating storytelling in vocabulary instruction can enhance student learning outcomes. Teachers are encouraged to use engaging and interactive methods to improve vocabulary skills, adapting strategies based on student needs and feedback.